Spatio‐temporal variation of biotic and abiotic stress agents determines seedling survival in assisted oak regeneration. Issue 12 (18th September 2019) - López‐Sánchez, Aida; Peláez, Marta; Dirzo, Rodolfo; Fernandes, G. Wilson; Seminatore, Mizael; Perea, Ramón
Abstract: Mediterranean oak woodlands are currently undergoing considerable anthropogenic changes that globally threaten their long‐term persistence. Restoration efforts via assisted regeneration depend on species traits and type of stress. However, how different sources of stress vary across space (microsites) and time (intra‐ and inter‐annual variation) for co‐occurring oak species remains largely unknown. We examined spatio‐temporal variation of biotic (herbivory, seed predation) and abiotic (drought) stress agents to evaluate seedling survival across different regeneration microsites, and considering two climatically contrasting years. We used two co‐occurring species of contrasting ecology and leaf traits in California oak woodlands: the deciduous Quercus lobata (valley oak) and the evergreen Q. agrifolia (coast live oak). Most oak seedlings (98.8%) suffered from some type of stress. For both species, summer drought was the main cause of mortality, followed by rodent damage, ungulate browsing and insect damage. Rodents represented the predominant biotic stress, as all rodent‐affected seedlings eventually died. Interactions among stress factors were nuanced: insect and ungulate‐browsing stresses were greater during dry year, whereas rodent damage was similar in dry and average years. Intra‐annually, rodent damage was the main stress agent in early spring, whereas water stress and ungulate‐browsing were greater from late spring to early fall. Plant species traits were also determinant: overall, the evergreen species had greater survival probability than the deciduous one. Across microsites, water stress showed higher occurrence in open grassland habitats, while rodent damage was prevalent under palatable shrubs and ungulate browsing under conspecific trees. Shrub and tree cover reduced damage attributed to water stress but increased rodent and ungulate damage, respectively. Interestingly, lower water stress but higher rodent damage was found further inside the shrub cover. Synthesis and applications . Intra‐ and inter‐annual variation are critical determinants of stress type and intensity on oak recruitment. Spatial variation (microsite identity) is highly useful to manipulate stress agent impact. We conclude that assisted regeneration should consider not only the predominance and lethality of each stress type and microsite, but also the interactions thereof and thus manipulate protective microsites accordingly. Abstract : Intra‐ and inter‐annual variation are critical determinants of stress type and intensity on oak recruitment. Spatial variation (microsite identity) is highly useful to manipulate stress agent impact. We conclude that assisted regeneration should consider not only the predominance and lethality of each stress type and microsite, but also the interactions thereof and thus manipulate protective microsites accordingly.